2004
DOI: 10.3201/eid1001.020572
|View full text |Cite
|
Sign up to set email alerts
|

SalmonellaEnteritidis Infections, United States, 1985–1999

Abstract: Salmonella enterica serotype Enteritidis emerged as an important illness during the 1980s. Investigations showed that consumption of undercooked eggs was the major risk factor for disease, and a variety of prevention and control efforts were initiated during the 1990s. We describe sporadic infections and outbreaks of S. Enteritidis in the United States from 1985 through 1999 and discuss prevention and control efforts. After reaching a high of 3.9 per 100,000 population in 1995, S. Enteritidis infections declin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
175
1
8

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 262 publications
(187 citation statements)
references
References 13 publications
3
175
1
8
Order By: Relevance
“…S. Enteritidis is passed to humans mainly via handling and consumption of contaminated poultry meat and eggs (De Buck et al, 2004;Kimura et al, 2004;Little et al, 2008;Marcus et al, 2004;Patrick et al, 2004;Snow et al, 2007). For instance, eggs and egg-containing products were implicated as primary vehicles of S. Enteritidis infection in 298 (80 %) of the 371 known-source outbreaks reported to the Centers for Disease Control and Prevention from 1985 to 1999 (Patrick et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…S. Enteritidis is passed to humans mainly via handling and consumption of contaminated poultry meat and eggs (De Buck et al, 2004;Kimura et al, 2004;Little et al, 2008;Marcus et al, 2004;Patrick et al, 2004;Snow et al, 2007). For instance, eggs and egg-containing products were implicated as primary vehicles of S. Enteritidis infection in 298 (80 %) of the 371 known-source outbreaks reported to the Centers for Disease Control and Prevention from 1985 to 1999 (Patrick et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Poultry is considered the single largest reservoir of S. Enteritidis and most risk attribution studies have identified poultry and poultry products as the major source of human infection. S. Enteritidis is passed to humans mainly via handling and consumption of contaminated poultry meat and eggs (De Buck et al, 2004;Kimura et al, 2004;Little et al, 2008;Marcus et al, 2004;Patrick et al, 2004;Snow et al, 2007). For instance, eggs and egg-containing products were implicated as primary vehicles of S. Enteritidis Abbreviations: MLVA, multi-locus variable-number tandem repeat analysis; PI, post-infection; SPI, Salmonella pathogenicity island; TEM, transmission electron microscopy; TTSS, type III secretion system.…”
mentioning
confidence: 99%
“…The incidence of human salmonellosis has increased greatly over the last 20 years and this can largely be attributed to an epidemics of S. enteritidis phage types 4 in poultry in many countries (Barrow et al [1], Guard-Petter [13], CDC [6,7], and Patrick et al [26]). Transmission to hens may originate from contaminated food, water, or from transmission by wild animals.…”
Section: Introductionmentioning
confidence: 99%
“…Salmonella is one of the major sources of toxic infection in humans in France and in United states (Bouvet et al [3] and Patrick et al [26]). The incidence of human salmonellosis has increased greatly over the last 20 years and this can largely be attributed to an epidemics of S. enteritidis phage types 4 in poultry in many countries (Barrow et al [1], Guard-Petter [13], CDC [6,7], and Patrick et al [26]).…”
Section: Introductionmentioning
confidence: 99%
“…From 1996 to 1999, Salmonella Enteritidis (SE) illness rates declined 48% [9]. Contamination of egg products by SE is the most commonly identified source of human foodborne illness [26]. Of the many serovars of Salmonellae, SE is commonly associated with foodborne illness in Japan, as in other industrial countries [13,27,28].…”
mentioning
confidence: 99%